Morainal Bank Evolution and Impact on Terminus Dynamics During a Tidewater Glacier Stillstand. Issue 11 (26th October 2020) - Eidam, E. F.; Sutherland, D. A.; Duncan, D.; Kienholz, C.; Amundson, J. M.; Motyka, R. J.
Abstract: Sedimentary processes are known to help facilitate tidewater glacier advance, but their role in modulating retreat is uncertain and poorly quantified. In this study we use repeated seafloor bathymetric surveys and satellite‐derived terminus positions from LeConte Glacier, Alaska, to evaluate the evolution of a morainal bank and related changes in terminus dynamics over a 17‐year period. The glacier experienced a rapid retreat between 1994 and 1999, before stabilizing at a constriction in the fjord. Since then, the glacier terminus has remained stabilized while constructing a morainal bank up to 140 m high in water depths of 240–260 m, with rates of sediment delivery of 3.3 × 10 5 to 3.8 × 10 5  m 3  a −1 . Based on repeated interannual surveys between 2016 and 2018, the moraine is a dynamic feature characterized by push ridges, evidence of active gravity flows, and bulldozing by the glacier at rates of up to meters per day. Beginning in 2016, the summertime terminus has become increasingly retracted, revealing a newly emerging basin potentially signaling the onset of renewed retreat. Between 2000 and 2016, the growing moraine reduced the exposed submarine area of the terminus by up to 22%, altered the geometry of the terminus during seasonal advances, and altered the terminus stress balance. These feedbacks for calving, melting, and ice flow likely represent mechanisms whereby moraine growth may delay glacier retreat, in a system where readvance is unlikely. Key Points: A new morainal bank up to 140 m high grew in 17 years at LeConte Glacier (southeast Alaska), during a glacier stillstand at a constriction Repeated multibeam surveys have highlighted dynamic processes of moraine sediment delivery, failure, and reworking by ice In cases where moraine development does not facilitate glacier readvance, it may still influence the retreat history